Intravitreal Devices for the Treatment of Vitreous Inflammation. (5th September 2012) - Christoforidis, John B.; Chang, Susie; Jiang, Angela; Wang, Jillian; Cebulla, Colleen M.
Abstract : The eye is a well-suited organ for local delivery of therapeutics to treat vitreous inflammation as well as other pathologic conditions that induce visual loss. Several conditions are particularly challenging to treat and often require chronic courses of therapy. The use of implantable intravitreal devices for drug delivery is an emerging field in the treatment of vitreous inflammation as well as other ophthalmologic diseases. There are unique challenges in the design of these devices which include implants, polymers, and micro- and nanoparticles. This paper reviews current and investigational drug delivery systems for treating vitreous inflammation as well as other pathologic conditions that induce visual loss. The use of nonbiodegradable devices such as polyvinyl alcohol-ethylene vinyl acetate polymers and polysulfone capillary fibers, and biodegradable devices such as polylactic acid, polyglycolic acid, and polylactic-co-glycolic acid, polycaprolactones, and polyanhydrides are reviewed. Clinically used implantable devices for therapeutic agents including ganciclovir, fluocinolone acetonide, triamcinolone acetonide, and dexamethasone are described. Finally, recently developed investigational particulate drug delivery systems in the form of liposomes, microspheres, and nanoparticles are examined.